2011
DOI: 10.1039/c0cc00656d
|View full text |Cite
|
Sign up to set email alerts
|

Anion receptor chemistry

Abstract: This article looks back at advances made in anion complexation since the turn of the millennium and ahead to the application of receptors in areas such as organocatalysis and nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
147
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(149 citation statements)
references
References 72 publications
2
147
0
Order By: Relevance
“…In the compounds containing nitro substituents (20b and 21b) a chargetransfer fluorescent state is formed resulting in quenched fluorescence. This gives rise to an ON-OFF fluorescence response for 20a and 21a, and an OFF-ON response for 20b and 21b upon the addition of acid, and the magnitude of the response depends on the nature of the acid (anion) with a larger response seen for HCl than for CF 3 COOH. Subsequent studies on derivatives of 19 containing various functionalities, revealed that the presence of electron withdrawing groups in 2,6-bis-(anilinoethynyl)pyridine bisureas in general transforms this class of compounds into ''switch on'' fluorescent chloride sensors.…”
Section: Derivatives Of Compoundmentioning
confidence: 99%
See 3 more Smart Citations
“…In the compounds containing nitro substituents (20b and 21b) a chargetransfer fluorescent state is formed resulting in quenched fluorescence. This gives rise to an ON-OFF fluorescence response for 20a and 21a, and an OFF-ON response for 20b and 21b upon the addition of acid, and the magnitude of the response depends on the nature of the acid (anion) with a larger response seen for HCl than for CF 3 COOH. Subsequent studies on derivatives of 19 containing various functionalities, revealed that the presence of electron withdrawing groups in 2,6-bis-(anilinoethynyl)pyridine bisureas in general transforms this class of compounds into ''switch on'' fluorescent chloride sensors.…”
Section: Derivatives Of Compoundmentioning
confidence: 99%
“…22). 16 These complexes exhibit intense luminescence in the solid state and in THF solutions, which was assigned to the 3 (pp*) excited state of the acetylide ligands. The authors found that changing the urea substituent could modify the anion binding strength in THF, with electron withdrawing groups (such as -NO 2 in 22) resulting in the strongest anion binding due to the increased acidity of the urea NH groups.…”
Section: Derivatives Of Compoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the advent of supramolecular chemistry in the 1980s, considerable effort has been invested in developing molecules that possess defined, predictable recognition properties [5][6][7] . Special focus has been placed on macrocyclic molecules, which have been shown to possess remarkable recognition properties with respect to anions 8 , cations 9 and small neutral molecules 10 . However, owing to a size discrepancy between host and guest molecules that is typically one to two orders of magnitude, applications with larger targets, such as proteins 2,11,12 , are limited.…”
mentioning
confidence: 99%